Liver transplantation: survival and indexes of donor-recipient matching - Silveira,Fábio (2021)
SUMMARY OBJECTIVE: The aim of this study was to determine the prospective capacity and impact of donor risk index, preallocation survival outcomes following liver transplant, donor model for end-stage liver disease, and balance of risk on patients’ 30-day survival after liver transplantation. METHODS: We prospectively analyzed patient survival in a multicentric observational cohort of adult liver transplantation through the year of 2019 at the state of Paraná, Brazil. The receiver operating characteristic curve, the area under the curve, and the best cutoff point (i.e., the Youden’s index) were estimated to analyze the prognostic value of each index. RESULTS: In total, 252 liver transplants were included with an average model for end-stage liver disease score of 21.17 and a 30-day survival of 79.76%. The donor risk index was the only prognostic variable with no relation to patients’ 30-day mortality model for end-stage liver disease and donor model for end-stage liver disease have no prognostic value on receiver operating characteristic curve, but preallocation survival outcomes following liver transplant, survival outcomes following liver transplant, and balance of risk presented good relationship with this observation. The cutoff value was estimated in 11-12 points for balance of risk and 9-12 for preallocation survival outcomes following liver transplant and survival outcomes following liver transplant. The 30-day survival for the group of transplants with scores up to 12 points (n=172) in all the three indexes was 87.79%, and for those transplants with scores higher than 12 it was 36.36%. CONCLUSIONS: The 30-day survival is 79.76%, and balance of risk, survival outcomes following liver transplant, and preallocation survival outcomes following liver transplant are the good prognostic indexes. The cutoff value of 12 points has clinical usefulness to predict the post-liver transplantation results.